Effectiveness of Interventions to Reduce Potentially Inappropriate Medication in Older Patients: A Systematic Review - Rodrigues, Daniela A.; Plácido, Ana I.; Mateos-Campos, Ramona; Figueiras, Adolfo; Herdeiro, Maria Teresa; Roque, Fátima (Frontiers in Pharmacology, 2022)
Background: Age-related multiple comorbidities prone older adults to the use of potentially inappropriate medicines (PIM) resulting in an increased risk of adverse events. Several strategies have been emerged to support PIM prescription and a huge number of interventions to reduce PIM have been proposed. This work aims to analyze the effectiveness of PIM interventions directed to older adults. Methods: A systematic review was performed searching the literature in the MEDLINE PubMed, EMBASE, and Cochrane scientific databases for interventional studies that assessed the PIM interventions in older adults (≥ 65 years). Results: Forty-seven articles were included, involving 52 to 124802 patients. Various types of interventions were analyzed such as medication review, educational strategies, clinical decision support system, organizational and multifaceted approaches. In the hospital, the most successful intervention was medication review (75.0%) while in primary care, the analysis of all included studies revealed that educational strategies were the most effective. However, the analysis of interventions that have greater evidence by its design was inconclusive. Conclusion: The results obtained in this work suggested that PIM-setting-directed interventions should be developed to promote the wellbeing of the patients through PIM reduction. Although the data obtained suggested that medication review was the most assertive strategies to decrease the number of PIM in hospital, more studies are necessary.